PERBANDINGAN DAYA SAING PRODUK GONDORUKEM DI PASAR INTERNASIONAL - Achmad Fachrodji; Ujang Sumarwan; Endang Suhendang; Harianto Harianto (Jurnal Manajemen & Agribisnis, 2009)
A high value non-wood product which is currently highly demanded in the local and international market is the Gondorukem (Gondorukem), produced from heating the pine’s tree gum (Pinus merkusii Junk). The constraint that we deal with is the fluctuation Gondorukem’s price which is triggered by the behavior of the Chinese industrialist since China is the biggest producer of Gondorukem. This research is aimed to compare the Gondorukem’s competitive advantage point a view from the industry, enterprises and countries’ among China, Brazil and Indonesia. The study is not only about comparing the Pine forest as a natural resource and measuring its productivity per hectare, but also observing the productivity and efficiency of the workers in each country. The analysis of industrial competitiveness is measured by using RCA# index, and the production cost and profit margin ratio is used to measure competitiveness among the enterprises. It can be concluded that China has the largest area of sap-tapped pine forest and Brazil is the highest for its forest productivity and workers’ efficiency, however Indonesia has the highest ratio of production cost and profit margin among the other countries. In term of the value of RCA# during the year of observation 2001 up to 2008, China exceeded Indonesia and Brazil. It’s expected by this research that Indonesia will be able to intensify the currently sap-tapped areas and expand the production area (extensive efforts) by utilizing the pine forest outside Java. It’s also proposed to increase the production by working on research about pine tree which produces more sap, performing comparative study to Brazil and raising up the wage of the sap-tapped workers.